Karakteristik Morfologi dan Uji Kandungan Nutrisi Pisang Batu (Musa balbisiana Colla) di Kabupaten Kuantan Singingi - Slamet Prayogi; Fitmawati Fitmawati; Nery Sofiyanti (Jurusan Biologi FMIPA Universitas Cenderawasih, 2016)
Musa balbisiana Colla in Kuantan Singingi Regency can survive from the disease that cause banana in many other areas loss their diversity. Currently, there is no information about the diversity of M. balbisiana from Kuantan Singingi. The purposes of this study were to record, characterize, and measure the diversity of M. balbisiana from Kuantan Singingi based on the morphological characters. M. balbisiana Colla samples were collected from three locations in kuantan singingi, i.e. Pangean, Cerenti, and Inuman. A total of 88 morphological characters of M. balbisiana were analyzed. The UPGMA analysis was conducted to find out the diversity of M. balbisiana. The result showed that there were six M. balbisiana cultivars, namely Aceh, Bungo, Kara, Jambi, Nipah, and Beluluk which were found in this study. The similarity coefficient values of these six banana cultivars was ranged from 63-89 %. Cluster analysis based on 88 morphological characters of M. balbisiana produced dendogram with 2 primary groups at percentage of similarity values of 66 %. Kara cultivar contained the highest carbohydrates, vitamin C, fiber and sodium content, while aceh cultivar had the highest potassium content. Key words: diversity, Kuantan Singingi, morphology, M. balbisiana, nutrient content